2003
DOI: 10.1097/01.alc.0000056620.98842.e6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Efficiency in Stimulant Abusers With and Without Alcohol Dependence

Abstract: As expected, substance abuse was associated with cognitive inefficiency. More importantly, these findings suggest that the cognitive effects of chronic stimulant abuse are not additive with those of alcohol abuse. That is, singly addicted stimulant abusers demonstrated similar or greater neurocognitive impairments than individuals who abuse alcohol and stimulants concurrently. The reason for this pattern is speculative but may be attributed to alcohol's opposing actions on cerebrovascular effects brought on by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 66 publications
5
28
0
Order By: Relevance
“…First, deficits in cognitive function following chronic exposure to METH have been attributed to impairments in frontostriatal systems. These include, for example, impairments in abstraction and cognitive flexibility (Kalechstein et al, 2003;Lawton-Craddock et al, 2003;Simon et al, 2002), cognitive inhibition Simon et al, 2002), working memory (Kalechstein et al, 2003;Rippeth et al, 2002), psychomotor processing speed (Kalechstein et al, 2003;Lawton-Craddock et al, 2003;Rippeth et al, 2002;Simon et al, 2002;Volkow et al, 2001a;Volkow et al, 2001c) and decision-making processes (Paulus et al, 2003). In addition, structural and functional changes in the cortex have been identified using a variety of imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…First, deficits in cognitive function following chronic exposure to METH have been attributed to impairments in frontostriatal systems. These include, for example, impairments in abstraction and cognitive flexibility (Kalechstein et al, 2003;Lawton-Craddock et al, 2003;Simon et al, 2002), cognitive inhibition Simon et al, 2002), working memory (Kalechstein et al, 2003;Rippeth et al, 2002), psychomotor processing speed (Kalechstein et al, 2003;Lawton-Craddock et al, 2003;Rippeth et al, 2002;Simon et al, 2002;Volkow et al, 2001a;Volkow et al, 2001c) and decision-making processes (Paulus et al, 2003). In addition, structural and functional changes in the cortex have been identified using a variety of imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, on comparing different cognitive domains in three groups of former users (cocaine, alcohol and alcohol-cocaine) there were statistically significant differences only between ex-cocaine users and ex-alcohol users. In fact, the group of ex-cocaine users showed less mental flexibility (assessed through the Bexley-Maudsley Category Sorting Test), poorer short-term/ working memory for visual information and lower processing speed (assessed through the Sternberg Task and the Processing Speed Index [PSI] of the WAIS-R) than ex-alcohol users and consumers of both substances (Lawton-Craddock, Nixon & Tivis, 2003). Thus, the neuropsy-chological deficits in people that abuse cocaine and alcohol and would ot be as pronounced as in those that use cocaine exclusively.…”
Section: Sex and Concurrent Use Of Alcohol And Cocaine: Precipitants mentioning
confidence: 99%
“…Although the nature and level of impairment may vary considerably across individuals, studies have consistently reported that AUD are specifically associated with dysfunction in cognitive efficiency Parsons, 1991, 1992;Lawton-Craddock et al, 2003;Nixon and Parsons, 1991;Nixon et al, 1995), executive skills (Bechara et al, 2001;Ihara et al, 2000;Moselhy et al, 2001;Sullivan et al, 2000b), learning and memory (Beatty et al, 1996;Brandt et al, 1983;Di Sclafani et al, 1995;Fama et al, 2004;Fein et al, 1990;Munro et al, 2000;Ratti et al, 1999;Rourke and Grant, 1999), processing speed (Davies et al, 2005;Parsons, 1998;Schulte et al, 2005), visuospatial skills (Beatty et al, 1996;Munro et al, 2000;Sullivan et al, 2000b), working memory (Brandt et al, 1983;Ratti et al, 1999), and gait and postural stability (Sullivan, 2003;Sullivan et al, 1995Sullivan et al, , 2000b. In those who manifest neurocognitive dysfunction after acute detoxification, variable levels of recovery are apparent with short-term (i.e., 1-5 months; Mann et al, 1999;Munro et al, 2000), intermediate-term (i.e., 6-12 months; Munro et al, 2000), and long-term abstinence from alcohol (i.e., 41 year; Fein et al, 2006;Mann et al, 1999;Munro et al, 2000;Reed et al, 1992;Rourke and Grant, 1999;…”
Section: Hronic Alcohol Use Disorders (Aud;mentioning
confidence: 99%